England relations with the Osmanli caliphate during the reign of Elizabeth I - Noris, Muhammad Ashraf; Zakariya, Hafiz (IIUM Press, International Islamic University Malaysia, 2017)
This book focuses on trade and economic concerns and later discusses further the diplomatic and socio-political effects. Emphasising only on its early years from 1580 to 1602, the book draws from a series of data retrieved from archives, personal records or diaries and scholarly works. Consequently, we will highlight the unique relationship of these two distinct empires from both English and Osmanli court perspectives.